A novel cuproptosis-related prognostic lncRNA signature and lncRNA MIR31HG/miR-193a-3p/TNFRSF21 regulatory axis in lung adenocarcinoma - Mo, Xiaocong; Hu, Di; Yang, Pingshan; Li, Yin; Bashir, Shoaib; Nai, Aitao; Ma, Feng; Jia, Guoxia; Xu, Meng (Frontiers in Oncology, 2022)
Lung adenocarcinoma (LUAD) remains the most common subtype of lung malignancy. Cuproptosis is a newly identified cell death which could regulate tumor cell pro-liferation and progression. Long non-coding RNAs (LncRNAs) are key molecules and potential biomarkers for diagnosing and treating various diseases. However, the effects of cuproptosis-related lncRNAs on LUAD are still unclear. In our study, 7 cu-proptosis-related lncRNAs were selected to established a prognostic model using univariate Cox regression analysis, LASSO algorithm, and multivariate analysis. Fur-thermore, we evaluated that AC008764.2, AL022323.1, ELN-AS1 and LINC00578 were identified as protective lncRNAs, while AL031667.3, AL606489.1 and MIR31HG were identified as risk lncRNAs. The risk score calculated by the prognos-tic model proved to be an effective independent factor compared with other clinical features by Cox regression analyses (Univariate analysis: HR=1.065, 95% Cl=1.043-1.087, P<0.001; multivariate analysis: HR=1.067, 95% Cl = 1.044-1.091, P<0.001). In addition, both analyses (ROC and nomogram) were used to corroborate the accu-racy and reliability of this signature. The correlation between cuproptosis-related lncRNAs and immune microenvironment was elucidated, finding that 7 immune cells and 8 immune-correlated pathways were differentially expressed between two risk groups. Furthermore, our results also identified and verified the ceRNA of cu-proptosis-related lncRNA MIR31HG/miR-193a-3p/TNFRSF21 regulatory axis using bioinformatics tools. And MIR31HG was highly expressed in LUAD specimens or some LUAD cell lines. Inhibition of MIR31HG clearly reduce the proliferation, mi-gration and invasion of the LUAD cells. MIR31HG showed oncogenic features via sponging miR-193a-3p and tended to positively regulate TNFRSF21 expression. In a word, lncRNA MIR31HG acts as an oncogene in LUAD by targeting miR-193a-3p to modulate TNFRSF21, which may be beneficial to gene therapy of LUAD.